RECENT ADVANCES IN IMMUNOTHERAPY FOR TRIPLE-NEGATIVE BREAST CANCER - Maxmudov Yorqinbek Ulug‘bek o‘g‘li; Babayev Hamza Nurmatovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Triple-negative breast cancer (TNBC) represents a highly aggressive subtype of breast cancer lacking estrogen receptor, progesterone receptor, and HER2 expression, posing significant therapeutic challenges due to limited targeted treatment options. Recent advancements in immunotherapy, particularly immune checkpoint inhibitors (ICIs) such as pembrolizumab, have demonstrated promising efficacy in both earlystage and metastatic TNBC, often in combination with chemotherapy. This thesis reviews the current landscape of immunotherapy in TNBC, focusing on novel strategies including PD-1/PD-L1 inhibitors, CAR-T cell therapy, cancer vaccines, and combination regimens. Key clinical trials like KEYNOTE-522 and IMpassion130 highlight improved pathological complete response rates and progression-free survival, yet issues such as biomarker identification, resistance mechanisms, and immune-related adverse events remain critical areas of investigation. Emerging approaches, such as bispecific antibodies and oncolytic viruses, offer potential to overcome these barriers. This work underscores the high relevance of immunotherapy in addressing unmet needs in TNBC management, providing insights into future directions for personalized and more effective treatments.